The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00018-019-03089-2
|View full text |Cite
|
Sign up to set email alerts
|

The expression of circulating miR-504 in plasma is associated with EGFR mutation status in non-small-cell lung carcinoma patients

Abstract: MicroRNAs (miRNAs), key regulators of gene expression at the post-transcriptional level, are grossly misregulated in some human cancers, including non-small-cell lung carcinoma (NSCLC). The aberrant expression of specific miRNAs results in the abnormal regulation of key components of signalling pathways in tumour cells. MiRNA levels and the activity of the gene targets, including oncogenes and tumour suppressors, produce feedback that changes miRNA expression levels and indicates the cell’s genetic activity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Nearly all primary DDR-induced effectors are regulated by miRNA and interact through their RNA-binding motifs in response to DSBs [126]. MiRNAs regulate, for example, H2AX (miRNA 24 and 138 [135,136]), PARP1 (miRNA-7-5p [137]), ATM (miRNA 18a and 421 [138]), ATM and DNA-PK (miRNA 101 [139]), BRCA1 (miRNA 182 [140]), RAD51 (miRNA 193b, 103 and 107 [141]), BRCA2 (miRNA 1245 [142]), RAD52 (miRNA 302a [143]), and P53 (miRNA 125b and 504 [144,145]). Actual models propose that ncRNAs facilitate DNA repair, either by the hybridization of sncRNA to broken DNA via DDX1 and DHX9 (dead-box helicases) to form specific sequences propagating repair pathways or by the hybridization of lncRNA via RAD52-strand invasion, generating a template for high-fidelity repair [146,147].…”
Section: Ncrnas As Emerging Regulatorsmentioning
confidence: 99%
“…Nearly all primary DDR-induced effectors are regulated by miRNA and interact through their RNA-binding motifs in response to DSBs [126]. MiRNAs regulate, for example, H2AX (miRNA 24 and 138 [135,136]), PARP1 (miRNA-7-5p [137]), ATM (miRNA 18a and 421 [138]), ATM and DNA-PK (miRNA 101 [139]), BRCA1 (miRNA 182 [140]), RAD51 (miRNA 193b, 103 and 107 [141]), BRCA2 (miRNA 1245 [142]), RAD52 (miRNA 302a [143]), and P53 (miRNA 125b and 504 [144,145]). Actual models propose that ncRNAs facilitate DNA repair, either by the hybridization of sncRNA to broken DNA via DDX1 and DHX9 (dead-box helicases) to form specific sequences propagating repair pathways or by the hybridization of lncRNA via RAD52-strand invasion, generating a template for high-fidelity repair [146,147].…”
Section: Ncrnas As Emerging Regulatorsmentioning
confidence: 99%
“…In patients with progressive disease, the expression level of MiRNA-10b increased compared to patients with complete remission or disease stability ( p = 0.001), while miRNA-21 had no prognostic effect on disease progression ( p = 0.720). However, Szpechcinski et al [ 98 ] found no significant differences of miRNA-10b and miRNA-21 expression level between NSCLC patients with or without EGFR mutations. The plasma miR-504 expression level in EGFR-mutated NSCLC patients was higher than those without EGFR mutations ( p = 0.0072).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…A large body of evidence has indicated the robust diagnostic accuracy of miRNAs in patients with mutated-EGFR versus wild-type EGFR. In accordance, the receiver operating curve unveiled the potential diagnostic value (AUC = 0.81, p < 0.0001) of circulating miR-504 in characterizing patients of EGFR exon 19 deletions from wild-type EGFR normalized to miR-191 [161]. Also, using a miRNA array profiling analysis, T790M/L858R-mutated lung cancer was found to have 20 up-regulated miRNAs, including miR-1 and miR-196a, compared to EGFR wild-type lung cancer [162].…”
Section: Specific Mirna Expression Patterns Affect the Behavior Of Egfr-mutated Nsclcmentioning
confidence: 69%